Cahokia: Urbanization, Metabolism, and Collapse - Tainter, Joseph A. (Frontiers in Sustainable Cities, 2019)
Cahokia in the 12th century A.D. was the largest metropolitan area and the most complex political system in North America north of Mexico. Its metabolism depended on an area of high natural and agricultural productivity. As it grew, Cahokia absorbed much of the rural population, transforming their labor from agriculture to public works. As Cahokia collapsed, this population first reoccupied the countryside, then left the region. Cahokia’s sustaining area was largely abandoned for centuries, suggesting that environmental degradation had made the region unsuitable for settlement, let alone the ability to support a metropolis. Factors pertinent to understanding the collapse of Cahokia include the societal metabolism, complexity, level of public works, the status of the support population, growth within the elite stratum, and trends in the American Bottom environment.